Mitral Repair for Mitral Prolapse: Comparison of Thoracoscopic Minimally-Invasive and Conventional Approaches Using Propensity Score. (9th April 2021) - Ascaso Arbona, Maria; Sandoval, Elena; Muro, Anna; Quintana, Eduard; Alcocer, Jorge; Barriuso, Clemente; Pomar, Jose Luis; Sitges, Marta; Castella, Manuel; Pereda, Daniel
Abstract : Objective : Surgical repair remains the standard treatment for severe mitral regurgitation (MR) due to mitral prolapse. Minimally-invasive mitral valve surgery (MIMVS) has been increasingly performed but still is the minority, with lack of solid evidence on its superiority over conventional surgery. Our objectives were to compare the results of MIMVS and conventional surgery. Methods : Retrospective review of all patients treated in our center with degenerative severe MR (November 2011 – May 2020). Patients with previous mitral surgery and those requiring concomitant procedures other than atrial fibrillation ablation were excluded. Two groups were compared: MIMVS (minimally invasive surgery) and Open (full median sternotomy), in a cohort of matched (1:1; nearest neighbor) pairs using propensity score (PS) methods. Results : 286 consecutive patients met the inclusion criteria (MIMVS:183, Open:103). There were no significant differences preoperatively, except for lower age, NYHA III-IV and EuroSCOREII in the MIMVS group. In both groups, around 40% of patients presented with anterior or bileaflet prolapse, with no differences in repair techniques used. After PS matching, a cohort of 93 matched pairs was selected and all basal differences were balanced. Comparisons showed that despite bypass and cross-clamp times were higher (+32 and +21m; p<0.001), MIMVS presented shorter mechanical ventilation (0 vs. 6h; p<0.01), ICU stay (1.8 vs. 2.5d; p=0.02), higher hemoglobin (11 vs. 10mg/dL; p<0.02) and less renal failure (1 vs. 8%; p:0.03). There were no differences in mortality, repair rate or MR grade at discharge. During follow-up (median 2.8 years), there were no significant differences in the degree of recurrent MR and reoperation. Conclusions : Surgical repair of mitral prolapse is possible in most cases with low perioperative morbimortality and excellent mid-term results. MIMVS can be performed without compromising perioperative outcomes, repair rate and durability, while providing shorter ICU and mechanical ventilation duration, less blood loss and renal failure.